A retrospective study investigating the effects of outpatient physiotherapy on lower back pain in Bangladesh - Islam, Muhammad Shahidul; Mamin, Firoz Ahmed (Asian Journal of Medical and Biological Research, 2018)
Low Back Pain (LBP) is a widespread global health problem. Almost 80% of people suffer from this condition at some point in their life. Management of LBP is a challenge for health care professionals. Out of all management strategies Physiotherapy is commonly and widely used around the globe for treating patients with LBP.A large number of people seek physiotherapy intervention for their LBP in Bangladesh however, studies regarding their treatment outcomes following physiotherapy are not available. This study was a retrospective, descriptive study of patients’ with Chronic Low Back Pain (CLBP) attending physiotherapy. The objective of this study was to investigate the level of pain and functional limitation following physiotherapy intervention. Information regarding 1,000 patients with LBP was retrieved from patient records in the Physiotherapy department at the Centre for the Rehabilitation of the Paralysed (CRP). Outcomes investigating pain and function were recorded and analysed. 63% of all participants were female. Pain was significantly reduced among patients with CLBP after receiving physiotherapy. Extension and flexion of the lumbar spine were lost in about 80% and 56% of patients respectively. Movements of the lumbar spine were improved after physiotherapy. Nearly 50% of patients reported improvements of more than 75% after receiving physiotherapy for LBP. Patients with CLBP had different characteristics. In this study it was not possible to record all necessary information. In general most of the patients’ outcomes were improved after receiving physiotherapy intervention. Asian J. Med. Biol. Res. December 2018, 4(4): 337-342